Chronobiological aspects of adult-onset Crohn disease - Mikulecký, Miroslav; Rovenský, Jozef; Kmecová, Z (Wiener klinische Wochenschrift, 2005)
PURPOSE: To study the time course of Crohn disease and its signs. To compare the results with the world literature and draw conclusions for practice. BASIC PROCEDURES: Fifty-six patients were studied retrospectively: 31 males aged 19-48 years with disease duration 1-8 years, and 25 females aged 21-65 with disease duration 1-13 years. The disease was active (Crohn disease activity index > 150) in 25 patients and inactive in 31. Plasma levels of interleukin-6 (normal upper value 8 pg/ml) were investigated with radioimmunoassay. Bone mineral density was measured as the T-score (normal range between -1 and 0 standard deviations) in the forearm using dual-energy X-ray absorptiometry. The seasonality of births of the patients in relation to the total Slovak population and seasonality of severity of three important disease signs were examined with Halberg cosinor regression. The dependence of the signs on age and duration of disease was evaluated using quadratic regression. Results are presented as 95% confidence intervals (for means) and 95% tolerance intervals (for individuals). The level of statistical significance was set at alpha = 0.05. MAIN FINDINGS: Significant seasonality in births was found: decreased frequency in May-June and increased frequency in September-January. Significant spring elevation of interleukin-6 levels, accompanied by significant spring rise of the disease activity index and by decrease of bone density, is described. Among patients with active disease, interleukin-6 levels significantly increased up to the age of 41 years, whereas linear increase of disease activity during aging was on the borderline level of significance in the same subgroup. No significant age trend was encountered in T-score for either subgroup. The same was true for interleukin-6 and disease activity versus duration. Significant decrease in T-score paralleled disease duration up to seven years in the subgroup with active disease. PRINCIPAL CONCLUSIONS: The course of Crohn disease is influenced by time, including the seasons of the year. However, this does not find full agreement in the world literature, probably because of geographic, socioeconomic and epidemiologic differences, as well as varying approaches in method. In practice, regular monitoring of the time course is necessary in provision of appropriately timed treatment.
Keywords: dospělí; Chronobiology Phenomena; regresní analýza; Slovakia; roční období; Absorptiometry, Photon; absorpční fotometrie; Crohn Disease; Slovenská republika; Risk Factors; mužské pohlaví; referenční hodnoty; Crohnova nemoc; Adult; Statistics as Topic; Interleukin-6; rizikové faktory; kostní denzita; Seasons; Regression Analysis; ženské pohlaví; statistika jako téma; interleukin-6; chronobiologické jevy; Reference Values; Aged; senioři; Bone Density; Male; Female